B-chromosomes in two Brazilian populations of Dendropsophus nanus (Anura, Hylidae) - Medeiros, Lilian R.; Rossa-Feres, Denise C. [UNESP]; Jim, Jorge [UNESP]; Recco-Pimentel, Shirlei M. (Sociedade Brasileira de Genética, 2006)
We report on the presence of B-chromosomes in two populations of Dendropsophus nanus (= Hyla nana Boulenger, 1889) from São Paulo State, Brazil. Such chromosomes were observed in 4 out of 43 specimens (9.3%) and in 9 out of 15 specimens (60%) from the municipalities of Nova Aliança and Botucatu, respectively. The karyotype 2n = 30 + 1B found in D. nanus was similar to that of other species with 2n = 30 chromosomes, except for the presence of an additional small telocentric chromosome. In one specimen from Botucatu, cells with one to three extra chromosomes were observed. These B-chromosomes appeared as univalent in meiosis I and did not bear a nucleolar organizer region or exhibit constitutive heterochromatin.
Keywords: Anura, b-chromosome; Cytogenetic; Dendropsophus; supernumerary chromosome